Legal rules of technology transfer in Asia - HEATH, Christopher (Institutional Knowledge at Singapore Management University, 2002)
Despite the harmonizing effect of TRIPS and intellectual property law in general, technology transfer remains firmly rooted in domestic contract law and public policy. However, similarities in legal culture across many national borders keep this problem to a minimum – until we approach the technologically advanced countries of East Asia. For practitioners worldwide working with technology transfer in this culturally heterogeneous part of the world, Legal Rules of Technology Transfer in Asia is a godsend.For each of nine significant technology market jurisdictions – the PRC, Taiwan, Japan, Korea, Vietnam, Thailand, Malaysia, Singapore and Indonesia – this nuts-and-bolts approach to the applicable national rules provides all necessary legal information and guidance. Country chapters by local authorities are structured to cover the following essential factors: government policy on technological research and transfer; intellectual property system; licensing agreements; registration and notification; dispute resolution; tax considerations; transfer of patents; choice of law questions; franchising; publicity and merchandising; anti-trust rules. ...and many other invaluable details to help lawyers and business persons avoid pitfalls and make the most of the technology transfer opportunities available in these countries.Two introductory chapters provide a much-needed perspective on technology transfer in the context of the world trade regime as it especially affects East Asia, with an emphasis on the trend to clarify and strengthen anti-trust rules. A concluding chapter surveys the market anthropology of the region and offers an expert assessment of the probable future development of technology transfer trade in the region.With its first-hand, in-depth, country-by-country analysis, and its firm grasp on a diversity of relevant legal and cultural issues, Legal Rules of Technology Transfer in Asia is unexcelled for desktop use in offices handling East Asian trade in technology products.